EVALUTION OF CENTRIFUGAL PUMP WORK ON DIESEL –TYPE ROVATTI - K. S. Al-Obaidy; N. S. Kadhem (مجلة الأنبار للعلوم الزراعية)
The aim of this research is to study the performance of centrifugal pump kind ruvatti (5×6)" using the diesel engine          (DEUTZ), in hot weather conditions located in Iraq. The experiment was conducted at the University of Baghdad, Iraq by using sedimentation tanks during 2023. The characteristics of centrifugal pump were increased pump speed that influenced on the discharge, the time of waterpower, fuel consumption, and exhausted temperature. Three deliveries of delivery head levels were used, which included 2.5, 3., and 3.5 bar besides two speeds which were 1500 and 1700 rmp. The results illustrated that the increased pump speed led to increasing discharge, the time of waterpower, fuel consumption, and exhausted temperature. While the increase in the delivery delivery head led to a decline in discharge, the time of waterpower, fuel consumption, and exhausted temperature. In order to extend the engine life the researchers recommended running the pump in the early morning or late afternoon. The reason behind that related to the cooling system of the engine is air cooling not water cooling